Chimerism analysis using next generation sequencing. Issue 1 (December 2019) - Minuti, B.; Lari, A.; Iozzi, S.; Palchetti, S.; Boschi, B.; Gerundino, F.; Pelo, E.; Ricci, U.
Abstract: Hematopoietic stem cell transplantation (HSCT) is the predominant curative treatment for many malignant and non-malignant haematological diseases. Early detection of graft rejection and disease relapse following HSCT improves patient outcomes by allowing treatment to be initiated as quickly as possible. In order to evaluate the level of donor engraftment, mixed chimerism levels must be carefully monitored after transplantation. Short-tandem repeat (STR) genotyping is widely used to determine the proportions of donor and recipient cells after HSCT. In this study, Devyser Chimerism NGS kit in combination with a MiSeq System was introduced in our laboratory for monitoring HSCT. This system is a complete workflow solution for labs, combining a reliable testing process with a designed for-purpose analytical software. Up to 24 informative markers in a recipient/donor pair distributed through the human genome have strong discriminative power with low bias from ethnic parameters. These IND/DEL genetic markers with population independent discriminative power are distributed across 17 chromosomes and were further selected to allow sensitive detection combined with accurate and precise quantification of mixed chimerism. Streamlined, simple and robust NGS workflow uses just one multiplex PCR reaction per patient sample. Minimal hands-on time reduces assay complexity and risk of sample contamination and mix-up. User-friendly, designed-for-purpose software perfectly complements testing kit with an automatic detection of informative markers. Insertion/deletion (indel) polymorphisms have been used in the fields of forensic investigations owing to the advantages of their low mutation rates, widespread distributions in the human genome and small amplicon sizes. Thus, forensic efficiency evaluation of this system for forensic individual identification will be also tested.